Possible Beneficial Effects of Fresh Pomegranate Juice in SARS-CoV-2 Infection Conditions - Saleem Ali Banihani (Journal of Nutrition and Metabolism)
Rather than the prophylactic vaccination, any effective synthetic, natural, or nutritional therapy or regimen that may cure or remedy, albeit partially, the complications of SARS-CoV-2 should be highly acknowledged. Here, we reviewed and discussed possible beneficial biological effects of pomegranate juice in such diseased condition of viral infection based on the current published evidence (direct and indirect) and owing to the robust evidence that fresh pomegranate juice is highly rich with unique bioactive compounds that are approved in various occasions to be effective in several chronic diseased conditions. All related references that serve our aim are accessed through available electronic databases, particularly PubMed and Scopus. In summary, there is accepted evidence that pomegranate juice may be beneficial in SARS-CoV-2 infection conditions, especially for patients with the clinical history of chronic diseases such as hypertension, cardiovascular disease, diabetes, and cancer. However, the interventional studies that directly probe and confirm the effectiveness of fresh pomegranate juice in the management of SARS-CoV-2 infection are mandatory.